AN EXPLORATORY GROUNDED THEORY OF BREASTFEEDING AMONG WOMEN WITH OPIOID USE DISORDER AND THEIR SUPPORT PERSONS - Cook, Kristy J. (East Carolina University, 2019)
With over 16 million women using opioids in the United States, neonatal abstinence syndrome (NAS) is increasing, and evidence suggests that NAS may be alleviated by breastfeeding. Yet, many women with opioid use disorder (OUD) experience stigma related to breastfeeding that potentially influences their decisions surrounding breastfeeding. No theoretical framework was identified that explained how perceived stigma influences breastfeeding decision-making in this population. Hence, the purpose of this study was to explore how women with OUD perceive breastfeeding, how stigma influences their breastfeeding decisions, and how support person perceptions influence breastfeeding among women with OUD. A grounded theory study was conducted with 10 women in treatment for OUD who were between 18 and 54 years of age and who breastfed a child in the last three years. Women were recruited from a drug rehabilitation therapy agency, a high-risk obstetrical office, and a major medical center. Each woman was asked to identify a breastfeeding support person. Data were generated from in-depth interviews of the women and their support persons, then coded in three iterative and progressive phases: initial, focused, and theoretical, leading to a theoretical model. Memos and field notes were written, and a dyad profile was developed to analyze data from the dyad perspective. Current professional organization guidelines on breastfeeding were reviewed to inform this study. The women interviewed for this study were White, with an average age of 30. Most had some college but were unemployed and had one to six pregnancies each. Symptom management or social and environmental factors led the women through a pain-prescription or street drug pathway before they hit rock bottom and began recovery. The overarching theme was Breastfeeding Decision-Making in an Addiction Trajectory. This was characterized by the Recovery-Relapse Cycle and Breastworks. Women had multiple Recovery-Relapse Cycle experiences, which involved seeking, initiating, and maintaining recovery and at times relapse, that influenced breastfeeding decisions. Breastworks describes the empowerment of women for maternal breastfeeding decisions with the goal of protecting the infant. Support persons were White with an average age of 39; all had some college and most worked full-time. Support persons expressed an uncertainty about breastfeeding with OUD related to the infant's health and mother's potential to relapse. Yet this uncertainty did not deter them from providing both physical and emotional support to these breastfeeding women. Uncertainty may be evident to women with OUD through good intentions of their support persons that are negatively perceived. Furthermore, such support person uncertainty and healthcare provider insensitivity may be perceived as stigma towards women with OUD, thus decreasing Breastworks effectiveness and risking newborn well-being. This study provides unique theoretical concepts that may be incorporated into the care of women with OUD, from preconception to postpartum, to support breastfeeding decision-making and infant well-being. Implications include development of a mobile breastfeeding education application, incorporation of breastfeeding guidelines into continuing education, involving successfully recovered women as community health workers, and expansion of this study.
Keywords: Stigma; Breast Feeding; Opioid-Related Disorders; Female; Grounded Theory; Pregnancy; Postnatal Care